RETRACTED: Effect of Bimetal Element Doping on the Low-Temperature Activity of Manganese-Based Catalysts for NH3-SCR - Li, Haixia; Zhang, Shuaibo; Zhang, Anchao; Zhang, Xinmin; Sun, Zhijun; Yang, Changze; Zhu, Qifeng (Frontiers in Chemistry, 2022)
Graphical Abstract